One-step solvothermal preparation of Fe-doped Ni0.85Se/NF: An efficient catalyst for the oxygen evolution reaction - Longqi Zhu; Runze Wang; Chen Wang; Shuhan Yang; Haizhen Liu; Bo Xing; Honghui Cheng; Kuikui Wang (ChemPhysMater)
Metal–cation doping is a fundamental strategy for enhancing catalyst performance. Fe-doped Ni0.85Se/NF (Fe-Ni0.85Se/NF) nanoparticles were prepared at 80 °C via Fe2+ etching method. The addition of Fe altered the coordination environment of the Ni species along with the catalyst's morphology, creating additional active sites. Notably, the synergistic interaction between the bimetallic components augmented the built-in activity and accelerated reaction kinetics. The Fe-Ni0.85Se/NF electrocatalysts demonstrated remarkable catalytic activity for the oxygen evolution reaction (OER), with an acceptable overpotential of 276 mV and a Tafel slope of 58.1 mV dec−1 at 100 mA cm−2. Moreover, they demonstrated exceptional durability. In situ Raman and X-ray photoelectron spectroscopy (XPS) analyses showed that the excellent OER performance stemmed from the reconstruction-induced hydroxyl oxide. This study offers a novel approach for streamlining the synthesis procedures and reducing the experimental costs for developing high-efficiency electrocatalysts.